Evaluasi Overhaul terhadap Efisiensi Boiler Unit 1 PLTU Banjarsari - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Alif Adiyanto (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
The boiler is a major component in a steam power plant because it converts feedwater into high-pressure and high-temperature steam for turbine operation. Boiler efficiency decreases when heat-transfer surfaces are dirty, combustion support equipment is not optimal, or operating instruments are inaccurate. This article evaluates the effect of overhaul on Boiler Unit 1 at PLTU Banjarsari using performance-test data at 125 MW. Two calculation approaches are used: the direct method and the indirect or heat-loss method. The direct-method efficiency increased from 67.65% before overhaul to 70.05% after overhaul, indicating a 2.40 percentage-point improvement. The indirect-method efficiency increased from 83.55% to 87.21%, indicating a 3.66 percentage-point improvement. The most relevant technical improvements were cleaning of boiler tubes, repair of a leaking superheater drain pipe, and calibration of the feedwater flow meter. The dry flue-gas loss decreased from 5.034% to 2.765%, while specific coal consumption decreased from 0.611 kg/kWh to 0.590 kg/kWh. These results show that overhaul improves heat utilization and supports more economical boiler operation.